ANALYSIS OF THE INFLUENCE OF FINANCIAL RATIOS TOWARDS PROFIT GROWTH (Study on LQ-45 Firms on BEI in 2011 – 2013 Periods) - Soebangkit, Nico Arfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
When taking economic decisions, investors can make fundamental analysis as one of the considerations. One of the things that are valued in fundamental analysis is earnings growth rates. Profit growth is inseparable from the company's performance as reflected in its financial ratios. This research was conducted to obtain empirical evidence about the influence of financial ratio variables by using some form of ratio such as Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TAT), Net Profit Margin (NPM), Gross Profit Margin (GPM) to the profit growth. The samples of this study are non-financial companies listed on LQ-45 in the period 2011 - 2013. The method used in data processing is multiple regression analysis. Results from this study indicate that the variable Total Assets Turnover (TAT), Net Profit Margin (NPM), and the Gross Profit Margin (GPM) have significant effect on profit growth. While variable Current Ratio (CR) and Debt to Equity Ratio (DER) have no significant effect on profit growth. The five variables used in this study, Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TAT), Net Profit Margin (NPM), Gross Profit Margin (GPM) simultaneously influence significantly the growth of the profit. The predictive capacity of these five variables simultaneously is 13.8%. Keywords: Financial Ratios, Profit Growth, Financial Report Company Performance